1997
DOI: 10.1002/bjs.1800841007
|View full text |Cite
|
Sign up to set email alerts
|

Duplex assessment of run-off before femorocrural reconstruction

Abstract: Duplex imaging is superior to arteriography for preoperative assessment of distal run-off for femorocrural reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Evaluation of the lower leg (crural) and pedal arteries has been one of the latest advancements of the DS technique (Figs 4 and 5). Important features of this application are the evaluation of PTA treatment options (28) and suitability of the crural arteries as run‐off for femoro‐distal bypasses (39).…”
Section: Duplex Scanning Of the Tibial Peroneal And Pedal Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the lower leg (crural) and pedal arteries has been one of the latest advancements of the DS technique (Figs 4 and 5). Important features of this application are the evaluation of PTA treatment options (28) and suitability of the crural arteries as run‐off for femoro‐distal bypasses (39).…”
Section: Duplex Scanning Of the Tibial Peroneal And Pedal Arteriesmentioning
confidence: 99%
“…This classification was found to correlate well with angiography, as illustrated by a kappa value above 0.60 to detect a crural occlusion or to assess the optimum crural run‐off vessel (41–43). Furthermore, it was proven that colour‐flow DS shows an accuracy that is at least as good as angiography for the prediction of the best outflow targets for lower extremity vascular reconstructions (13, 39), and that also in this arterial segment angiography should be used only selectively (44). The interobserver reproducibility of DS was found to be good within the popliteal and tibial arteries and moderate within the pedal arteries (40).…”
Section: Duplex Scanning Of the Tibial Peroneal And Pedal Arteriesmentioning
confidence: 99%
“…With technical advances in vascular surgical techniques it is now possible to successfully bypass stenoses and obstructions of the lower leg and to make distal anastomoses of bypass grafts to arteries around the ankle or in the foot (6). In contrast to patients with intermittent claudication, imaging outflow arteries is therefore an essential part of the imaging workup and potentially limb‐saving in patients with chronic critical ischaemia, particularly when it is taken into account that iaDSA is known to fail in visualizing patent crural and foot arteries, that are demonstrated with other modalities (7–9).…”
Section: The Purpose Of Imaging In the Workup Of Peripheral Arterial mentioning
confidence: 99%
“…Since 1987 numerous studies from both the United States and Europe have demonstrated that duplex ultrasound scanning (DU) is comparable to contrast arteriography (CA) for imaging tibial and peroneal arteries in patients with critical lower extremity ischemia. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, only Ligush et al 13 and Lujan et al 15 have prospectively compared DU and CA findings with the operation actually performed, the true standard. To confirm their suggestion that DU alone could be adequate for planning and performing bypass grafting at the level of the tibia, we compared how accurately surgeons using either DU or CA alone selected the artery actually chosen as the bypass recipient by the operating surgeon familiar with both DU and CA data.…”
mentioning
confidence: 99%